MicroRNAs in the epigenetic regulation of disease progression in Parkinson’s disease - Selvakumar, Sushmaa Chandralekha; Preethi, K. Auxzilia; Tusubira, Deusdedit; Sekar, Durairaj (Frontiers in Cellular Neuroscience, 2022)
Parkinson's disease (PD) is a multifactorial neurodegenerative condition with symptoms such as resting tremor, rigidity, bradykinesia (slowness of moment), and postural instability. Neuroinflammation plays a significant part in the onset and progression of neurodegeneration in a wide range of disorders, including PD. The loss of dopaminergic neurons in the substantia nigra (SN) is thought to be the primary cause of PD disease progression. However, other neurotransmitter systems like serotoninergic, glutamatergic, noradrenergic, adrenergic, cholinergic, tryptaminergic, and peptidergic appear to be affected as well. Epigenetic regulation of gene expression is emerging as an influencing factor in the pathophysiology of PD. In recent years, epigenetic regulation by microRNAs (miRNAs) has been discovered to play an important function in the disease progression of PD. This review explores the role of miRNAs and their signalling pathways in regulating gene expression from development through neurodegeneration and how these mechanisms are linked to the pathophysiology of PD, emphasising potential therapeutic interventions.